Age and tectonic significance of the Benton pluton, Eel River area, west-central New Brunswick, Canada - Fyffe, Leslie R.; Ludman, Allan; McFarlane, Christopher (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2023)
The Benton pluton, located in the Eel River area of west-central New Brunswick, Canada, consists of two components—the Caldwell Brook quartz monzonite and Dugan Road monzogranite. Field relations suggest that the two are essentially coeval, the Dugan Road being slightly younger. The Benton pluton intrudes Cambrian to Early Ordovician sedimentary rocks of the Woodstock Group and overlying Early to Middle Ordovician calc-alkaline rhyolitic, andesitic, dacitic, and basaltic rocks of the lower Meductic Group. A new U–Pb (LA-ICP-MS) zircon age of 467 ± 2. Ma indicates that the Dugan Road monzogranite component of the Benton pluton was emplaced during the Middle Ordovician (late Dapingian to early Darriwilian). The Dugan Road monzogranite is ca. 7 million years younger than the nearby arc-related Connell Mountain tonalite and Gibson granodiorite, and ca. 13 million years younger than arc- related volcanic rocks of the Porten Road Formation, the oldest unit of the Meductic Group. The Benton pluton is interpreted to have been emplaced in an active extensional arc setting, coinciding with a shift in the focus of subduction-related volcanism from the Eel River area of New Brunswick to the Greenfield area of adjacent Maine, USA.